The landscape of multiscale transcriptomic networks and key regulators in Parkinson’s disease - Qian Wang (Nature Portfolio, 2019)
Parkinson’s disease (PD) is characterized by neurodegeneration associated with loss of dopaminergic (DA) neurons and deposition of Lewy bodies. Here, Wang et al. use co-expression network analysis to pinpoint disease pathways and propose reduced expression of STMN2 as a cause of presynaptic function loss in PD.